Annual Plan 1971-72 Part-I Explanatory Memorandum Government of Tripura - Planning Commission (Planning Commission, 1971)
Tripura, which is now a Union Territory, is a State of great antiquity. Once a Princely State it claims to be the most ancient of all the former Princely States in India. It is a land of temples and tradition. Long hill ranges and deep forests has created a charming natural beauty. It is nice in its wealth of flora and fauna. Area of the Territory is above 10431 Sq. Kms. by length 183.5 Kms. and by width 112.7 Kms. being not easily communicable. The Territory is generally regarded as ore of the inaccessible, areas. Six principal ranges of hills rarely, Debtamura.
Development (Planning and Coordination) Department, Government of Tripura